Are Sage‐Grouse Fine‐Scale Specialists or Shrub‐Steppe Generalists?. Issue 4 (19th February 2020) - Smith, Joseph T.; Allred, Brady W.; Boyd, Chad S.; Carlson, John C.; Davies, Kirk W.; Hagen, Christian A.; Naugle, David E.; Olsen, Andrew C.; Tack, Jason D.
ABSTRACT: Sage‐grouse ( Centrocercus spp.) are influencing rapidly evolving land management policy in the western United States. Management objectives for fine‐scale vegetation characteristics (e.g., grass height >18 cm) have been adopted by land management agencies based on resource selection or relationships with fitness proxies reported among numerous habitat studies. Some managers, however, have questioned the appropriateness of these objectives. Moreover, it remains untested whether habitat–fitness relationships documented at fine scales (i.e., among individual nests within a study area) also apply at scales of management units (e.g., pastures or grazing allotments), which are many orders of magnitude larger. We employed meta‐analyses of studies published from 1991 to 2019 to help resolve the role of fine‐scale vegetation structure in nest site selection and nest success across the geographic range of greater sage‐grouse ( C. urophasianus ) and evaluate the validity of established habitat management objectives. Specifically, we incorporated effects of study design and functional responses to resource availability in meta‐regression models linking vegetation structure to nest site selection, and used a novel meta‐analytic approach to simultaneously model vegetation structure and its relationship to nest success. Our approach tested habitat relationships at a range‐wide extent and a grain size closely matching scales at which agencies make management decisions. We found moderate, but context‐dependent, effects of shrub characteristics and weak effects of herbaceous vegetation on nest site selection. None of the tested vegetation characteristics were related to variation in nest success, suggesting nesting habitat–fitness relationships have been inappropriately extrapolated in developing range‐wide habitat management objectives. Our findings reveal surprising flexibility in habitat use for a species often depicted as having very particular fine‐scale habitat requirements, and cast doubt on the practice of adopting precise management objectives for vegetation structure based on findings of individual small‐scale field studies. © 2020 The Authors. The Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society. Abstract : Sage‐grouse offer an illustrative case of a common situation in which management objectives, based on informal synthesis of findings of small‐scale field studies, are applied across a species' range. Our meta‐analyses of sage‐grouse nesting studies revealed that widely adopted habitat management objectives prescribe a narrow range of conditions found in only a small subset of breeding habitats successfully exploited by the species across its range, and have no relationship to demographic performance.